PERFORMANCE AND DIFFICULTIES OF FAMILY NURSES IN THE PREVENTION OF DIABETIC FOOT (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objectives: To investigate the preventive assessment of the foot in patients with diabetes mellitus (DM) performed by nurses from the Family Health Strategy. Method: A descriptive-exploratory study, with a qualitative approach, carried out in Basic Health Units in the urban area of Floriano, state of Piauí, Brazil, with ten nurses from the Family Health Strategy. Data were obtained through remote interviews using a semi-structured script. For data analysis, the content analysis technique proposed by Deslandes et al. was used. Results: From this, the categories “Nurses’ actions in the prevention of diabetic foot” and “Factors that interfere in the preventive assessment of the feet” emerged. The preventive assessment of the feet in diabetic patients is partial, superficial and fragmented. Conclusion: It is necessary to train professionals for the development of preventive assessment of the diabetic foot, as well as the provision of necessary resources for this purpose.